Digital transformation and Public Procurement Performance: Analysing its Roles, Challenges and Opportunities in Developing Countries - Getrude John Danieli (Rescollacom (Research Collaborations Community), 2026)
Though adoption and use of digital technologies among developing countries is not impressive, digital transformation in public procurement offers considerable benefits like to enhance effectiveness, transparency and accountability plus cost reduction. The intention of the study is to investigate the roles, challenges and opportunities for digital transformation in public procurement in Tanzania as a case for developing countries. In this study, the independent variables were, digital infrastructure (INF), IT competence of procurement staffs (CMP), digital processes (DP) and digital technology (DT), whereas dependent variable was procurement performance indicated by Benefit-Cost Ratio (BCR). A descriptive cross-sectional design was used. A self-administered semi-structured questionnaire was developed to gather data from 280 respondents selected from 40 government entities, and an interview guide to conduct interview to six heads of procurement department and six heads of ICT units from selected government entities. The collected data were analysed using descriptive, multiple linear regression model and content analysis. The findings demonstrate that the extent public agencies have digitalised their procurement activities is moderate. The results of regression analysis point out that INF, CMP and DP have positive and significant association with BCR, excerpt DT has negative and non-significant. Therefore, it was concluded that, improving INF, CMP and DP enhances performance of public procurement. Moreover, various challenges such as insufficient infrastructure to support digitalisation, restricted access to technology, and low level of technical expertise among procurement staffs have been identified. This study has filled a knowledge gap regarding the role digital transformation in public procurement plays in Tanzania, and developing countries. Based on the findings this study recommends the improvement of digital infrastructure and technology, capacity building of procurement staffs through training and development programs, improve accessibility of digitalised services and update regulatory and legal frameworks for optimum digital application.